Pengembangan Lembar Kerja Siswa (LKS) Menggunakan Pendekatan Matematika Realistik Indonesia Berbasis Konteks Sumatera Selatan - Idul Adha; Rani Refianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to produce student worksheets (LKS) that are validity and practical, and have potential effects on student learning outcomes. The method in this study uses the modified Dick and Carey development method. LKS developed valid based on expert and practical response questionnaires based on student response questionnaires. The potential effects of LKS developed can be seen from the activities of students in working on the questions on the LKS, where students more easily understand the mathematical concepts contained in the LKS and use the concepts appropriately in solving the problems given. The results of the study Of the 23 students who were the subjects of the study obtained 11 people were in the excellent category or around 47.82%. Whereas there are 5 people in katerogy or around 21.73%, enough categories are obtained by 4 people or around 17.39% and the poor category is obtained by 3 people or around 13.04%. It can be concluded that LKS designed using a realistic Indonesian mathematical approach based on the context of South Sumatra has a potential effect on student learning outcomes. Keywords: PMRI, Student worksheet, Development